Közfoglalkoztatás, mint a munkanélküliség csökkentésére alkalmas egységes rendszer bemutatása - Oláh, Judit (Jelenkori Társadalmi és Gazdasági Folyamatok, 2014)
It is important to investigate labour market tools as employment policy is expected to reduce unemployment and the segmentation of the labour market, to decrease the intensifying unfavourable situation of vulnerable social groups, to help the geographical, employment and branch labour mobility and to improve productivity. I examine the role of public employment of the labour market tools. I introduce the development of public employment tools and detail that what effects the public employment has on the tendency of unemployment. The literature review in my research was compiled with the aim of a secondary research objective. In the literature review I deal with the introduction of the public employment as a tool for handling labour market crises in the countries of the European Union, as well as with the characteristics of the new system of public employment in Hungary. The numbers of those who are involved in the public employment program both at national and sub-regional levels forecast its significance and necessity under the present condition of the Hungarian economy.